Fluctuating environments impact thermal tolerance in an invasive insect species Bactrocera dorsalis (Diptera: Tephritidae) - Mutamiswa, Reyard; Tarusikirwa, Vimbai; Nyamukondiwa, Casper; Chidawanyika, Frank (Wiley, 2022)
The incidence and severity of environmental stressors associated with global climate change are increasing and insects frequently face variability in temperature and moisture regimes at variable spatio-temporal scales. Coincidental with this, is increased thermal and hydric stress on insects as warming increases vapour pressure deficit (VPD), the drying power of the air. While the effects of mean temperatures on fitness are widely documented, fluctuations in both temperature and relative humidity (RH) are largely unexplored. Here, we investigated the effects of dynamic temperature and RH fluctuations (around the mean [28°C; 65% RH]) on low and high thermal tolerance of laboratory-reared adult invasive Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), measured as critical thermal minima (CTmin), critical thermal maxima (CTmax), chill coma recovery time (CCRT) and heat knockdown time (HKDT). Our results show that increased environmental amplitude significantly influenced low and high temperature responses and varied across traits tested. The highest amplitude (δ12°C; 28% RH) compromised CTmin, CCRT and HKDT traits while enhancing CTmax. Similarly, acclimation to δ3°C; 7% RH compromised both low (CTmin and CCRT) and high (CTmax and HKDT) fitness traits. Variations in fitness reported here indicate significant roles of combined thermal and moisture fluctuations on B. dorsalis fitness suggesting caveats that are worthy considering when predicting species responses to climate change. These results are significant for B. dorsalis population phenology, management, quantifying vulnerability to climate variability and may help modelling future biogeographical patterns.